The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.21273/jashs.132.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Genetic Architecture of Fruit Quality Traits in Melon Using a Genomic Library of Near Isogenic Lines

Abstract: A melon (Cucumis melo L.) genomic library of near-isogenic lines derived from the cross between the Spanish cultivar Piel de Sapo and the exotic accession PI 161375 has been evaluated for fruit quality traits in four different locations. Traits evaluated were fruit weight, soluble solids content, maximum fruit diameter, fruit length, fruit shape index, ovary shape index, external color, and flesh color. Among these traits, soluble solids content showed the highest genotype × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
97
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 48 publications
18
97
0
5
Order By: Relevance
“…Recently, Feder et al [71] identified a Kelch domain-containing F-box protein regulating naringenin chalcone accumulation in melon rind producing the change from white to yellow rind. This gene (MELO3C011980, annotated as similar to F-box/kelch-repeat protein At1g23390) colocalizes with QTLs involved in the variation of external color in melons [72, 73]. In C. pepo , we found two genes annotated as F-box/kelch-repeat protein (Additional file 6) in the LOD peak regions of the MaRCo_4 QTL (CP32_ scaffold000022_600093-603383 and 624476-611084, best nr hit F-box/kelch-repeat protein At1g55270-like and At2g44130-like respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Feder et al [71] identified a Kelch domain-containing F-box protein regulating naringenin chalcone accumulation in melon rind producing the change from white to yellow rind. This gene (MELO3C011980, annotated as similar to F-box/kelch-repeat protein At1g23390) colocalizes with QTLs involved in the variation of external color in melons [72, 73]. In C. pepo , we found two genes annotated as F-box/kelch-repeat protein (Additional file 6) in the LOD peak regions of the MaRCo_4 QTL (CP32_ scaffold000022_600093-603383 and 624476-611084, best nr hit F-box/kelch-repeat protein At1g55270-like and At2g44130-like respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Other two minor QTLs (R 2  < 5%) involved in the variation of flesh color were also detected, although with significant E and G x E effect (Additional file 5) ( MaFCo_10 , 37.9 cM, CP32_scaffold000009_1923620-CP32_scaffold000009_2317405, and MaFCo_13 , 53.1 cM, CP32_scaffold000017_2743863-CP32_scaffold000108_169208) that can act modulating the effect of the major gene, as it has been also reported in melons [72, 73, 7880]. …”
Section: Resultsmentioning
confidence: 99%
“…(Group Inodorus)] genome (Eduardo, Arús, & Monforte, 2005) used in this study was described by Eduardo et al (2007). Eighteen NILs contained a single molecular markerdefined introgression from SC into the PS genetic background (Eduardo et al, 2007), and the rest had two or more. The introgressions from SC presented in this set of NILs covered at least 85% of melon genome.…”
Section: Plant Materialsmentioning
confidence: 99%
“…NILs were coded with the prefix ''SC" followed by x-y numbers and, in some cases, one or two z letters (SCx-y z, for example SC3-5ab): the first x number indicates the linkage group (LG), and the second number y indicates the number of the NIL within the LG. The letters indicates additional genetic facts: ''a", there is more than one introgression; ''b" the NIL has an introgression slightly different from the introgression of the NIL with the same number described in Eduardo et al (2005), although it covers the same genomic region; ''h", the introgression is heterozygous and ''d", part of the introgression is heterozygous (Eduardo et al, 2007). Although the mapping resolution of this population is not very high, it is sufficient for focusing research effort.…”
Section: Plant Materialsmentioning
confidence: 99%
“…SSR markers fromDanin-Poleg et al (2000, 2001), Fazio et al (2002,Chiba et al (2003),Ritchel et al (2004),Gonzalo et al (2005),Kong et al (2006Kong et al ( , 2007 andFukino et al (2007) b Linkage group number according toPerin et al (2002),Eduardo et al (2007),Cuevas et al (2008) andFukino et al …”
mentioning
confidence: 99%